2020
DOI: 10.1111/his.14191
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of novel ALKATI with ALK immunohistochemistry and clinical outcomes in metastatic melanoma

Abstract: Aims: Recently, a novel isoform of anaplastic lymphoma kinase, with alternative transcription initiation (ALK ATI), has been described in melanoma and is susceptible to targeted ALK-inhibitor therapy. Clinical outcomes of patients with ALK ATI mutated melanoma as well as correlation with immunohistochemical (IHC) methods have not yet been described. Methods and results: Clinicopathological characteristics were abstracted for 324 patients with metastatic melanoma (MM). IHC, fluorescence in-situ hybridisation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
1
0
4
Order By: Relevance
“…ALK plays an important role in the occurrence and metastasis of non–small cell lung cancer, malignant peritoneal mesothelioma, gynecologic clear cell carcinoma, melanoma, etc. [ 22 , 23 , 24 , 25 ]. As written in the previous part of this article, it was initially reported that approximately 80% of patients with Cowden syndrome had an identifiable germline PTEN mutation [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…ALK plays an important role in the occurrence and metastasis of non–small cell lung cancer, malignant peritoneal mesothelioma, gynecologic clear cell carcinoma, melanoma, etc. [ 22 , 23 , 24 , 25 ]. As written in the previous part of this article, it was initially reported that approximately 80% of patients with Cowden syndrome had an identifiable germline PTEN mutation [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…По данным K. K. Shah, экспрессия ALK ATI в метастатических опухолях оказалась ниже, чем в первичных, что может свидетельствовать о потере данной мутации с развитием болезни. Практически во всех исследованиях ингибиторы ALK работали при транслокации ALK в клетках меланомы [24].…”
Section: Discussionunclassified
“…исследовали 45 меланом методом полимеразной цепной реакции и обнаружили, что 24,4 % меланом экспрессировали ALK; в 7 из 45 меланом выявлена ALK ATI , причем гистологически это были абсолютно разные опухоли (3 узловые, 2 слизистые, 1 поверхностная и 1 акральная) [22]. Такие результаты обнадеживают, несмотря на малую выборку пациентов, так как секвенированиеслишком дорогостоящий метод для использования в рутинной практике, а ИГХ-метод имеет низкую чувствительность (55 %), по данным некоторых исследований [24].…”
Section: встречаемость Alk и методы исследованияunclassified
See 2 more Smart Citations